Pengaruh Sistem Informasi Inventory Pergudangan terhadap Kinerja Karyawan Bagian Operasional di PT. YCH Indonesia - Wardoyo Wicaksono; Cundo Harimurti (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
This study is carried out at PT.YCH Indonesia. The objective of this study is to analyze significance of influence of warehouse information system to performance of operational department’s employee at PT. YCH Indonesia. This study used quantitative research method by giving questionnaires to 71 respondents, computation and data analysis used SPSS progam version 16. From the data processing found a correlation value of 0.724, thereby it can be concluded that a correlation between inventory information system variable (X) toward employee performance (Y) has strong correlation. Result of R square (R2) value of 0.569 or in the amount of 56.9%, therefore it can be said that inventory information system variable has the influence in the amount of 56.9% and the remaining of 43.1% is another influence not subject to research. Result of test identified that t count is in the amount of 9.543, therefore H0 is rejected and H1 is accepted because tcount 9.543 > ttable 1.667 and can be said that inventory information system has significant influence to customer’s satisfaction. Result of test identified that tcount 4.592 thereby H0 is rejected and Ha accepted because tcount 4.592 > ttable 1.673 and significance 0.000 < 0.1, and can be said that warehouse inventory information system has significant influence to employee performance.